PHYSICOCHEMICAL CHARACTERIZATION AND STATISTICAL EVALUATION OF LOCALLY MODIFIED ADSORBENTS FOR VEGETABLE OIL BLEACHING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Efficient bleaching of vegetable oils is essential for improving product color, oxidative stability, and storage life. This study investigates the physicochemical properties and technological performance of activated bentonite (A1), kaolin-based adsorbent (A2), and a locally modified composite adsorbent (A3) applied in the bleaching of cottonseed and sunflower oils. Specific surface area (BET), pH, adsorption capacity, peroxide value, and color index (Lovibond scale) were determined. Statistical evaluation included regression modeling, analysis of variance (ANOVA), and error estimation.The modified composite adsorbent (A3) exhibited the highest surface area (238 m²/g) and adsorption capacity (94 mg/g), achieving 92% bleaching efficiency. A strong positive correlation between surface area and bleaching efficiency was established (R² = 0.94). ANOVA confirmed the statistically significant influence of adsorbent type (p < 0.05). The mean squared error ranged from 0.018 to 0.026, indicating high experimental reliability.The findings demonstrate that locally developed adsorbents can serve as cost-effective and sustainable alternatives to imported bleaching earths in industrial oil processing.